RANCANG BANGUN WEBSITE EVENT ORGANIZER ISEN MULANG YOUTH PALANGKA RAYA (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2017)
The internet technology has been progressed very rapidly along by the time. It has resultedone facility that is used in many aspects of living sector, known as website.Now, in the globalization era, website is used widely in many sectors of life such as education,social, health and business.This thesis aims to create an information website of Isen Mulang Youth Palangkaraya’sEvent Organizer which uses notepad++, script PHP and MySQL database that can be used inWindows operation system. The method that is used in collecting data such as interview by doingquestion and answer directly to the section that is connected to the object of the study. Directobservation is used to convey the information. That is progressing in Isen Mulang YouthPalangkaraya Event Organizer. The literature review in collecting data by learning literature booksabout plan and design of one system. System design and data base planning are used by data flowdiagram to create system model and entity relational diagram that describe the model of datarelation.It is hoped the presence of this website can help the Event Organizer in Conveying theinformation and publishing the Isen Mulang Youth Palangkaraya widely through internet so thathelping people getting information about Isen Mulang Youth Palangkaraya.